Argentina - Hamwee, Robert (London : Kuperard, 2015)
The second-largest country in South America, Argentina has been through great changes in recent years. Its journey from dictatorship to democracy has left many scars, but these are largely eclipsed by the pride and resilience of the Argentinian people, who have developed a style, a language, and a "joie de vivre" that are all their own. The political maelstroms the country has experienced have had a profound effect on its economy, its people, and its relationship with the rest of the world. Despite this, the generosity, warmth, and openness of the Argentinians continue to place Argentina at the top of any list of must-visit countries. Its unique geography provides a plethora of enticing and captivating destinations, from the mesmerizing wonders of the glaciers or the bucolic landscapes of the Andes valleys to the buzz and excitement of Buenos Aires, famous for its nightlife, gastronomy, and cultural life. This new, updated edition of "Culture Smart! Argentina" looks at the attitudes and values of the people today and how they have adapted to the challenges and events over the last decade. From their immense pride in an Argentinian pope, to their passion for football and their constant striving for political and economic stability, this book provides a key to understanding the richness and complexity of Argentinian culture. It focuses on their attitude to life, business, and family to help you adapt to their working style and practices, so that you know how to behave appropriately and what to expect in return. It touches upon how Argentinian identity has been shaped over time and the reasons behind many of the traditions, beliefs, and norms of these complicated but amazing people.
Includes bibliographical references (pages 164-165) and index.
Publication date as found on Amazon.com.
Keywords: Argentina -- Social life and customs -- 21st century -- Handbooks, manuals, etc; Etiquette -- Argentina -- Handbooks, manuals, etc; National characteristics, Argentine -- Handbooks, manuals, etc; Visitors, Foreign -- Argentina -- Life skills guides